Aramid paper for resin-infiltration-resistant honeycomb core material and preparation method of aramid paper

By preparing aramid paper with high temperature resistant meta-aramid chopped fibers and sprayed aramid nanofibers, the problems of existing aramid paper brittlement and tear strength after impregnation of resin are solved, and a honeycomb core material with good strength and toughness are achieved.

CN119900192AActive Publication Date: 2025-04-29YANTAI METASTAR SPECIAL PAPER
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510386545.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

Existing aramid paper is prone to brittleness after impregnation of resin, and the tear strength index is relatively low, making it difficult to meet the needs of high-end applications.

Method used

A preparation method for resin-resistant, impregnated, honeycomb core material is adopted. By mixing a high-temperature functional powder and the first dispersant with the meta-aramid polymer solution, wet spinning and heat treatment, high-temperature meta-aramid chopped fibers are prepared, and the tearing strength of aramid paper is improved by spraying aramid nanofibers and double-layer composite inclined paper machine.

Benefits of technology

It effectively improves the tearing strength of aramid paper, improves the problems of high brittleness and poor toughness of honeycomb core materials prepared by traditional aramid paper, and is suitable for the field of honeycombs for aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900192A_ABST
    Figure CN119900192A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aramid paper, in particular to aramid paper for a resin-infiltration-resistant honeycomb core material and a preparation method of the aramid paper for the resin-infiltration-resistant honeycomb core material, in the preparation process of the aramid paper for the resin-infiltration-resistant honeycomb core material, high-temperature-resistant meta-aramid chopped fibers, meta-aramid fibrids and aramid nanofibers are used as main raw materials for composite papermaking, meanwhile, a novel hot-pressing process of firstly carrying out high temperature and low pressure and then carrying out low temperature and high pressure after pre-drying is adopted, so that the prepared aramid paper has good resin wettability resistance and small impregnation sizing amount, the tearing strength can be kept at a relatively high level before and after resin impregnation, and the problems of high brittleness and poor toughness of a honeycomb core material prepared from traditional aramid paper can be effectively solved; the method is suitable for the field of aramid paper honeycombs for space flight and aviation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to aramid paper for resin impregnation resistant honeycomb core material and a preparation method thereof, belonging to the technical field of aramid paper. Background Art

[0002] With the continuous advancement of industrialization and technology, the demand for high-performance composite materials has gradually increased. Aramid honeycomb core material is a high-performance sandwich composite material that combines the excellent properties of aramid paper and the unique structure of honeycomb. It has many advantages such as light weight and high strength, flame retardancy and high temperature resistance, chemical corrosion resistance, good sound insulation and heat insulation performance, and excellent impact resistance. It is widely used in aerospace, automobile, construction and other fields. The processing process of aramid honeycomb core material is relatively complicated. It is generally prepared through processes such as gluing, lamination, pressing and curing, stretching and shaping, dipping and curing. Its main raw materials are aramid paper, core strip glue and impregnating resin. The processing process of honeycomb core material has high requirements on the overall performance of aramid paper, especially the tear strength index of aramid paper after impregnation with resin.

[0003] At present, most aramid paper products on the domestic market are prone to embrittlement after being impregnated with resin, and the tear strength index is generally low, resulting in poor tensile strength and low roller peeling strength of aramid honeycombs during application, making it difficult to meet high-end application requirements such as aerospace equipment. The reason is that, on the one hand, the interlayer bonding force of the fibers in conventional aramid paper is poor, resulting in a high porosity of aramid paper. During the process of impregnation of the honeycomb core material, excessive resin enters the interior of the aramid paper, causing the honeycomb to be brittle and poor in toughness. On the other hand, in the production process of aramid paper, the traditional high-temperature and high-pressure hot pressing process will cause a certain degree of damage to the main structure of the aramid fiber, limiting the effective transfer of stress between fibers, resulting in a significant decrease in the tear strength of the aramid paper after hot pressing. Therefore, the development of a resin-resistant aramid paper for honeycombs is an urgent issue to be solved.

[0004] Chinese patent application CN114211847A discloses a special aramid paper for aramid paper honeycomb and a preparation method thereof. Although the problem of aramid paper being impregnated with resin during the preparation of honeycomb core materials is solved by compounding meta-aramid paper with para-aramid paper, stratification is prone to occur during the application process, and the introduction of adhesives will also have an adverse effect on the gluing and dipping processes for preparing honeycomb core materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides an aramid paper for a resin-impregnation-resistant honeycomb core material and a preparation method thereof. The aramid paper has good resistance to resin impregnation, a small amount of impregnation glue, and a high tear strength before and after resin impregnation. The aramid paper can effectively improve the problems of high brittleness and poor toughness of honeycomb core materials prepared from traditional aramid paper, and can be applicable to the field of aramid paper honeycombs for aerospace.

[0006] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing aramid paper for resin-impregnated honeycomb core material, the preparation method comprising: S1, adding the high temperature resistant functional powder and the first dispersant into a solvent and mixing them evenly to obtain a dispersion containing the high temperature resistant functional powder; and mixing the dispersion containing the high temperature resistant functional powder and the meta-aramid polymer solution evenly to obtain a spinning solution; The high temperature resistant functional powder is aluminum diethylphosphinate powder and boron nitride powder; S2, spinning the spinning solution by wet spinning, and then going through a high-temperature coagulation bath, a room-temperature coagulation bath, washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; S3, preparing a high temperature resistant meta-aramid chopped fiber slurry by mixing the high temperature resistant meta-aramid chopped fiber in water; preparing meta-aramid fibrid into meta-aramid fibrid slurry; The high temperature resistant meta-aramid chopped fiber slurry and the meta-aramid fibrid slurry are uniformly mixed to obtain a mixed slurry; S4, sending the mixed slurry to a double-layer composite inclined wire paper machine for papermaking, after the bottom wire wet paper web is formed, spraying the aramid nanofiber dispersion on the upper surface of the bottom wire wet paper web, and then compounding it with the surface wire wet paper web, so that the aramid nanofiber is located between the bottom wire wet paper web and the surface wire wet paper web, and obtaining the aramid paper base paper after pressing and drying; S5. After being dried and preheated, the aramid base paper is subjected to two hot pressing processes to obtain the aramid paper for the resin impregnation resistant honeycomb core material.

[0007] Further, in step S1, the mass ratio of the aluminum diethylphosphinate powder to the boron nitride powder is 1:(2-3); The first dispersant is any one of polymethacrylic acid and polyvinyl pyrrolidone.

[0008] Furthermore, in step S1, the solvent in the meta-aramid polymer solution is N,N-dimethylformamide; the solvent for preparing the dispersion is N,N-dimethylformamide; The meta-aramid polymer solution has a solid content of 25-28% and a viscosity of 450-650P at 25°C; The mass content of the high temperature resistant functional powder in the dispersion is 20-35%, and the mass content of the first dispersant in the dispersion is 1.0-2.5%; The mass ratio of the dispersion to the meta-aramid polymer solution is 1:(13-18).

[0009] Further, in step S2, the temperature of the high temperature coagulation bath is 50-90°C, the high temperature coagulation bath is N,N-dimethylformamide and water, and the mass concentration of N,N-dimethylformamide in the coagulation bath is 28-32%; The temperature of the room temperature coagulation bath is 20-30° C. The room temperature coagulation bath is N,N-dimethylformamide and water. The mass concentration of N,N-dimethylformamide in the room temperature coagulation bath is 25-30%.

[0010] Furthermore, in step S2, the heat treatment temperature is 250-350°C; the oxygen plasma surface treatment equipment is an inductively coupled plasma generator, the treatment frequency is 1000-1300 Hz, and the treatment time is 8-10 min; the length of the high temperature resistant meta-aramid chopped fibers is 5-8 mm.

[0011] Further, in step S3, the preparation method of the high temperature resistant meta-aramid short fiber slurry is: putting the high temperature resistant meta-aramid short fiber into deionized water for stirring, adding a second dispersant to disperse and disperse uniformly, and obtaining a high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2%-1.0%, wherein the mass content of the second dispersant in the high temperature resistant meta-aramid short fiber slurry is 0.1-0.5%; the second dispersant is any one of polyethylene oxide and polyacrylamide; The preparation method of the meta-aramid fibrid slurry is as follows: the meta-aramid fibrid is emulsified by a high-speed shear emulsifier at a processing speed of 13000-15000 rpm for a processing time of 10-15 minutes, and then the meta-aramid fibrid is pulped and dispersed to prepare a meta-aramid fibrid slurry with a mass concentration of 0.5%-1.5%; the size distribution of the meta-aramid fibrid is 40-120 meshes.

[0012] Furthermore, the aramid nanofiber dispersion comprises aramid nanofibers and deionized water, wherein the mass fraction of aramid nanofibers in the aramid nanofiber dispersion is 0.05-0.20%; The aramid nanofiber is any one of meta-aramid nanofiber and para-aramid nanofiber, and the diameter of the aramid nanofiber is 40-100 nm.

[0013] Furthermore, in step S5, a drying tunnel type drying device is used for drying and preheating, and the drying and preheating temperature is 200-260°C; The two hot pressing steps include a first high-temperature and low-pressure hot pressing operation and a second low-temperature and high-pressure hot pressing operation. The temperature of the first high-temperature and low-pressure hot pressing operation is 290-340°C, the pressure is 120-180N / mm, and the vehicle speed is 15-30m / min; the temperature of the second low-temperature and high-pressure hot pressing operation is 230-270°C, the pressure is 350-400N / mm, and the vehicle speed is 15~30m / min.

[0014] Furthermore, in the process of preparing the aramid paper, the meta-aramid fibrids are 30-50 parts by weight, the high temperature resistant meta-aramid chopped fibers are 50-70 parts by weight, and the aramid nanofibers are 8-15 parts by weight.

[0015] The invention also discloses an aramid paper for a resin-impregnation-resistant honeycomb core material. The aramid paper is prepared according to the preparation method of the invention.

[0016] The beneficial effects of the present invention are: The present invention prepares a high temperature resistant meta-aramid chopped fiber, improves the high temperature resistance of the aramid fiber, reduces the damage to the strength and structure of the aramid fiber during the hot pressing process, and uses an oxygen plasma treatment method to perform surface treatment on the high temperature resistant meta-aramid chopped fiber, effectively improves the hydrophilicity and chemical reaction activity of the fiber without affecting the strength index of the chopped fiber, so that the dispersion effect of the chopped fiber and the bonding ability between the fibers are better. At the same time, the novel hot pressing process of pre-baking, first high temperature and low pressure, and then low temperature and high pressure is adopted to effectively improve the phenomenon that the tear strength of the aramid paper decreases significantly after hot pressing. Pre-baking can not only avoid the wrinkles caused by sudden shrinkage of the aramid paper after entering the high temperature and hot pressing environment, but also keep the aramid paper fully dry, and improve the problem of the decrease in tear strength caused by the swelling of the fiber due to moisture. The high temperature and low pressure treatment reduces the adverse effect of pressure on its tear strength performance while ensuring that the aramid paper is effectively plasticized due to the high temperature, and a second hot pressing low temperature and high pressure treatment is set to ensure that the basic indicators such as thickness and tightness of the aramid paper meet the requirements.

[0017] In addition, the present invention adds aramid nanofibers in the papermaking process by spraying. Aramid nanofibers are nanometer-scale fibers composed of aromatic polyamide molecules, with large specific surface area and high surface energy. The addition of aramid nanofibers can significantly improve the bonding force between fibers and the flexibility of aramid paper, and reduce the porosity of aramid paper as a whole, improving the situation of excessive impregnation and penetration of aramid paper when impregnating resin.

[0018] In summary, the aramid paper prepared by the present invention has good resistance to resin infiltration, a small amount of impregnation glue, and the tear strength can maintain a high level before and after resin impregnation, which can effectively improve the problems of high brittleness and poor toughness of honeycomb core materials prepared from traditional aramid paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a process flow chart for preparing the aramid paper. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0022] like Figure 1 As shown, a method for preparing aramid paper for resin impregnation resistant honeycomb core material, the preparation method is: S1, adding the high temperature resistant functional powder and the first dispersant into a solvent and mixing them evenly to obtain a dispersion containing the high temperature resistant functional powder; and mixing the dispersion containing the high temperature resistant functional powder and the meta-aramid polymer solution evenly to obtain a spinning solution; The high temperature resistant functional powder is aluminum diethylphosphinate powder and boron nitride powder; S2, spinning the spinning solution by wet spinning, and then going through a high-temperature coagulation bath, a room-temperature coagulation bath, washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; S3, preparing a high temperature resistant meta-aramid chopped fiber slurry by mixing the high temperature resistant meta-aramid chopped fiber in water; preparing meta-aramid fibrid into meta-aramid fibrid slurry; The high temperature resistant meta-aramid chopped fiber slurry and the meta-aramid fibrid slurry are uniformly mixed to obtain a mixed slurry; S4, sending the mixed slurry to a double-layer composite inclined wire paper machine for papermaking, after the bottom wire wet paper web is formed, spraying the aramid nanofiber dispersion on the upper surface of the bottom wire wet paper web, and then compounding it with the surface wire wet paper web, so that the aramid nanofiber is located between the bottom wire wet paper web and the surface wire wet paper web, and obtaining the aramid paper base paper after pressing and drying; S5. After being dried and preheated, the aramid base paper is subjected to two hot pressing processes to obtain the aramid paper for the resin impregnation resistant honeycomb core material.

[0023] Specifically, in step S1, the mass ratio of the aluminum diethylphosphinate powder to the boron nitride powder is 1:(2-3); The first dispersant is any one of polymethacrylic acid and polyvinyl pyrrolidone.

[0024] Specifically, in step S1, the solvent in the meta-aramid polymer solution is N,N-dimethylformamide; and the solvent for preparing the dispersion is N,N-dimethylformamide.

[0025] More specifically, the preparation method of the meta-aramid polymer solution is as follows: in a system where N,N-dimethylformamide is an organic solvent, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymer solution.

[0026] The meta-aramid polymer solution has a solid content of 25-28% and a viscosity of 450-650P at 25°C; The mass content of the high temperature resistant functional powder in the dispersion is 20-35%, and the mass content of the first dispersant in the dispersion is 1.0-2.5%; The mass ratio of the dispersion to the meta-aramid polymer solution is 1:(13-18).

[0027] Specifically, in step S2, the temperature of the high-temperature coagulation bath is 50-90°C, the high-temperature coagulation bath is N,N-dimethylformamide and water, and the mass concentration of N,N-dimethylformamide in the room temperature coagulation bath is 28-32%; The temperature of the room temperature coagulation bath is 20-30° C., the room temperature coagulation bath is N,N-dimethylformamide and water, and the mass concentration of N,N-dimethylformamide in the high temperature coagulation bath is 25-30%.

[0028] Specifically, in step S2, the heat treatment temperature is 250-350°C; the oxygen plasma surface treatment equipment is an inductively coupled plasma generator, the treatment frequency is 1000-1300 Hz, and the treatment time is 8-10 min; the length of the high temperature resistant meta-aramid chopped fibers is 5-8 mm.

[0029] Specifically, in step S3, the preparation method of the high temperature resistant meta-aramid short fiber slurry is: putting the high temperature resistant meta-aramid short fiber into deionized water for stirring, adding a second dispersant to disperse and disperse uniformly, and obtaining a high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2%-1.0%, wherein the mass content of the second dispersant in the high temperature resistant meta-aramid short fiber slurry is 0.1-0.5%; the second dispersant is any one of polyethylene oxide and polyacrylamide; The preparation method of the meta-aramid fibrid slurry is as follows: the meta-aramid fibrid is emulsified by a high-speed shear emulsifier at a processing speed of 13000-15000 rpm for a processing time of 10-15 minutes, and then the meta-aramid fibrid is pulped and dispersed to prepare a meta-aramid fibrid slurry with a mass concentration of 0.5%-1.5%; the size distribution of the meta-aramid fibrid is 40-120 meshes.

[0030] Specifically, the aramid nanofiber dispersion comprises aramid nanofibers and deionized water, wherein the mass fraction of aramid nanofibers in the aramid nanofiber dispersion is 0.05-0.20%; The aramid nanofiber is any one of meta-aramid nanofiber and para-aramid nanofiber, and the diameter of the aramid nanofiber is 40-100 nm.

[0031] Specifically, in step S5, a drying tunnel type drying device is used for drying and preheating, and the drying and preheating temperature is 200-260°C; The two hot pressing steps include a first high-temperature and low-pressure hot pressing operation and a second low-temperature and high-pressure hot pressing operation. The temperature of the first high-temperature and low-pressure hot pressing operation is 290-340°C, the pressure is 120-180N / mm, and the vehicle speed is 15-30m / min; the temperature of the second low-temperature and high-pressure hot pressing operation is 230-270°C, the pressure is 350-400N / mm, and the vehicle speed is 15~30m / min.

[0032] Specifically, in the process of preparing the aramid paper, the meta-aramid fibrids are 30-50 parts by weight, the high temperature resistant meta-aramid chopped fibers are 50-70 parts by weight, and the aramid nanofibers are 8-15 parts by weight.

[0033] Aramid paper for resin-impregnation-resistant honeycomb core material, wherein the aramid paper is prepared according to the preparation method of the present invention.

[0034] Sources of raw materials used in the embodiments of the present invention: N,N-dimethylformamide was provided by Wuhan Rongcan Biotechnology Co., Ltd.; calcium oxide was provided by Shenyang Ketuo Chemical Co., Ltd.; aluminum diethylphosphinate was provided by Hubei Hongjing Chemical Co., Ltd.; boron nitride powder was provided by Henan Xinzhiyuan Chemical Products Co., Ltd.; meta-aramid fiber precipitation, isophthaloyl chloride and metaphenylenediamine were provided by Taihe New Materials Group Co., Ltd.; polymethacrylic acid was provided by Hubei Tosoh Chemical Technology Co., Ltd.; polyvinyl pyrrolidone was provided by Hefei Tianjian Chemical Co., Ltd.; polyethylene oxide was provided by Suzhou Qihang Biotechnology Co., Ltd.; and polyacrylamide was provided by Shandong Tongli Chemical Co., Ltd. However, it does not constitute a limitation on the technical solution of the present invention.

[0035] Example 1 This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 40 parts of meta-precipitated fibers; 60 parts of high-temperature-resistant meta-aramid short fibers; and 10 parts of aramid nanofibers.

[0036] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out with isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out with calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 500P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 30%, and the mass content of the first dispersant in the dispersion is 1.5%.

[0037] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:15. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 80°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 27%; the temperature of the room-temperature coagulation bath is 30°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 300°C, the frequency of the oxygen plasma surface treatment is 1300 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 7 mm.

[0038] (4) The high temperature resistant meta-aramid short fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 15 min.

[0039] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.05%.

[0040] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing is completed, an aramid paper for a honeycomb core material resistant to resin impregnation is obtained. The set temperature of the drying channel drying device is 240°C, the temperature of the first hot pressing high temperature and low pressure is 320°C, the pressure is 150N / mm, and the vehicle speed is 20m / min, and the temperature of the second hot pressing low temperature and high pressure is 240°C, the pressure is 400N / mm, and the vehicle speed is 20m / min.

[0041] Example 2 This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 45 parts of meta-precipitated fibers; 55 parts of high-temperature-resistant meta-aramid short fibers; and 10 parts of aramid nanofibers.

[0042] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out with isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out with calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 500P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 30%, and the mass content of the first dispersant in the dispersion is 1.5%.

[0043] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:15. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 80°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 27%; the temperature of the room-temperature coagulation bath is 30°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 310°C, the frequency of the oxygen plasma surface treatment is 1100 Hz, and the treatment time is 8 minutes; the length of the high-temperature resistant meta-aramid short fibers is 7 mm.

[0044] (4) The high temperature resistant meta-aramid short fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 15 min.

[0045] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.05%.

[0046] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing is completed, an aramid paper for a honeycomb core material resistant to resin impregnation is obtained. The set temperature of the drying channel drying device is 240°C, the temperature of the first hot pressing high temperature and low pressure is 330°C, the pressure is 140N / mm, and the vehicle speed is 18m / min, and the temperature of the second hot pressing low temperature and high pressure is 240°C, the pressure is 380N / mm, and the vehicle speed is 18m / min.

[0047] Example 3 This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 55 parts of high-temperature-resistant meta-aramid short fibers; and 8 parts of aramid nanofibers.

[0048] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0049] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 80°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 28%; the temperature of the room-temperature coagulation bath is 30°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 300°C, the frequency of the oxygen plasma surface treatment is 1000 Hz, and the treatment time is 9 minutes; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0050] (4) The high temperature resistant meta-aramid short fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 15 min.

[0051] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 60 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.08%.

[0052] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing is completed, an aramid paper for a honeycomb core material resistant to resin impregnation is obtained. The set temperature of the drying channel drying device is 250°C, the temperature of the first hot pressing high temperature and low pressure is 310°C, the pressure is 160N / mm, and the vehicle speed is 19m / min, and the temperature of the second hot pressing low temperature and high pressure is 230°C, the pressure is 360N / mm, and the vehicle speed is 19m / min.

[0053] Example 4 This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 54 parts of high-temperature-resistant meta-aramid short fibers; and 9 parts of aramid nanofibers.

[0054] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the reaction is neutralized with calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 28% and a viscosity (25°C) of 550P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 35%, and the mass content of the first dispersant in the dispersion is 1.5%.

[0055] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:18. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 90°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 28%; the temperature of the room-temperature coagulation bath is 25°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 30%. The temperature of the heat treatment is 340°C, the frequency of the oxygen plasma surface treatment is 1200 Hz, and the treatment time is 8 minutes; the length of the high-temperature resistant meta-aramid short fibers is 5 mm.

[0056] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 12 min.

[0057] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.18%.

[0058] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing is completed, an aramid paper for a honeycomb core material resistant to resin impregnation is obtained. The set temperature of the drying channel drying device is 260°C, the temperature of the first hot pressing high temperature and low pressure is 340°C, the pressure is 180N / mm, and the vehicle speed is 15m / min, and the temperature of the second hot pressing low temperature and high pressure is 270°C, the pressure is 400N / mm, and the vehicle speed is 15m / min.

[0059] Example 5 This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0060] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0061] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0062] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0063] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0064] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, wherein the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing process is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing process is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing process is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0065] Comparative Example 1 The aramid paper for honeycomb core material was prepared by the same method as in Example 5, except that the aramid nanofibers were not sprayed during the papermaking process in Comparative Example 1. The specific experimental process is as follows: This comparative example illustrates an aramid paper for honeycomb core material, which is composed of the following raw materials in parts by weight: 50 parts of meta-deposition fibers; and 60 parts of high temperature resistant meta-aramid chopped fibers.

[0066] A method for preparing aramid paper for honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0067] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0068] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0069] (5) The mixed slurry from step (2) is sent to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, it is composited with the top wire wet paper web, and the aramid paper base paper is obtained by pressing and drying. (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing is completed, an aramid paper for a honeycomb core material resistant to resin impregnation is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing high temperature and low pressure is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing low temperature and high pressure is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0070] Comparative Example 2 The aramid paper for honeycomb core material was prepared by the same method as in Example 5, except that: this comparative example 2 did not use high temperature resistant meta-aramid short fibers, but used conventional meta-aramid short fibers of the same size. The specific experimental process is as follows: This comparative example illustrates an aramid paper for honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-deposition fibrils; 51 parts of conventional meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0071] A method for preparing aramid paper for honeycomb core material comprises the following steps: (1) conventional meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a conventional meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrid is emulsified, and then pulped and dispersed to obtain a meta-aramid fibrid slurry with a mass concentration of 0.5%; the conventional meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrid slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyacrylamide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0072] (2) The mixed slurry of step (1) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0073] (3) The aramid paper base obtained in step (2) is fully dried and preheated through a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, wherein the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing process is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing process is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing process is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0074] Comparative Example 3 The aramid paper for honeycomb core material was prepared by the same method as in Example 5, except that: in step (6) of this comparative example 3, two hot pressings were not performed, but only one hot pressing operation with high temperature and high pressure was performed, as follows: This ratio illustrates an aramid paper for a resin-impregnated honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0075] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0076] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0077] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0078] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0079] (6) The aramid paper obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for a hot pressing process, namely, a high-temperature and high-pressure hot pressing process. After the hot pressing is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the high-temperature and high-pressure hot pressing process is 310°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0080] Comparative Example 4 The aramid paper for honeycomb core material was prepared by the same method as in Example 5, except that: in step (6) of this comparative example 4, two hot pressings were not performed, but only one low-temperature and low-pressure hot pressing operation was performed, as follows: This ratio illustrates an aramid paper for a resin-impregnated honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0081] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0082] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0083] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0084] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0085] (6) The aramid paper obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for a hot pressing process, namely, a high-low-temperature and low-pressure hot pressing process. After the hot pressing is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the low-temperature and low-pressure hot pressing process is 240°C, the pressure is 170N / mm, and the vehicle speed is 25m / min.

[0086] Comparative Example 5 The aramid paper for honeycomb core material is prepared by the same method as in Example 5, except that the high temperature resistant functional powder in this comparative example 5 is only boron nitride powder, which is as follows: This ratio illustrates an aramid paper for a resin-impregnated honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0087] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is boron nitride powder; the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0088] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0089] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0090] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0091] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, wherein the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing process is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing process is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing process is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0092] Comparative Example 6 The aramid paper for honeycomb core material is prepared by the same method as in Example 5, except that: the high temperature resistant functional powder in this comparative example 6 is only aluminum diethylphosphinate powder, which is as follows: This ratio illustrates an aramid paper for a resin-impregnated honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0093] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Add the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stir evenly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is aluminum diethylphosphinate powder; the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0094] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0095] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are emulsified, and then pulped and dispersed to obtain a meta-aramid fibrils slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibrils slurry with a mass concentration of 0.5% are mixed, and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide, and the rotation speed of the emulsification treatment is 15000 rpm, and the time is 14 min.

[0096] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0097] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, wherein the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing process is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing process is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing process is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0098] Comparative Example 7 The aramid paper for honeycomb core material was prepared by the same method as in Example 5, except that the meta-aramid fibrids in this comparative example 7 were not subjected to emulsification treatment, as follows: This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0099] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0100] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, water washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, the frequency of the oxygen plasma surface treatment is 1400 Hz, and the treatment time is 10 min; the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0101] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are beaten and dispersed to obtain a meta-aramid fibril slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibril slurry with a mass concentration of 0.5% are mixed and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide.

[0102] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0103] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, wherein the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing process is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing process is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing process is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0104] Comparative Example 8 The aramid paper for honeycomb core material was prepared by the same method as in Example 5, except that: in the process of preparing the high temperature resistant meta-aramid chopped fibers described in Comparative Example 8, no oxygen plasma surface treatment was performed, as follows: This embodiment illustrates an aramid paper for a resin-impregnation-resistant honeycomb core material, which is composed of the following raw materials in parts by weight: 47 parts of meta-precipitated fibers; 51 parts of high-temperature-resistant meta-aramid short fibers; and 12 parts of aramid nanofibers.

[0105] A method for preparing aramid paper for resin-impregnation-resistant honeycomb core material comprises the following steps: (1) In a nitrogen atmosphere, solution polymerization is carried out using isophthaloyl chloride and meta-phenylenediamine in a system with N,N-dimethylformamide as an organic solvent to obtain a meta-aromatic polyamide solution containing isophthaloyl meta-phenylenediamine as a repeating unit, and hydrochloric acid generated by the neutralization reaction is carried out using calcium oxide to obtain a meta-aramid polymerization liquid; the meta-aramid polymerization liquid has a solid content of 25% and a viscosity (25°C) of 600P; (2) Adding the high temperature resistant functional powder and the first dispersant into N,N-dimethylformamide solvent and stirring uniformly to obtain a dispersion containing the high temperature resistant functional powder; the high temperature resistant functional powder is a combination of diethyl phosphinate aluminum powder and boron nitride powder, the corresponding weight ratio is 1:3, and the first dispersant is polymethacrylic acid. The mass content of the high temperature resistant functional powder in the dispersion is 32%, and the mass content of the first dispersant in the dispersion is 2.0%.

[0106] (3) The meta-aramid polymer solution in step (1) and the dispersion solution in step (2) are mixed and stirred uniformly to obtain a spinning solution. The mass ratio of the dispersion solution to the meta-aramid polymer solution is 1:16. The spinning solution is spun by wet spinning, and then goes through a high-temperature coagulation bath, a room-temperature coagulation bath, washing, drying, heat treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; the temperature of the high-temperature coagulation bath is 85°C, and the mass concentration of N,N-dimethylformamide in the high-temperature coagulation bath is 30%; the temperature of the room-temperature coagulation bath is 29°C, and the mass concentration of N,N-dimethylformamide in the room-temperature coagulation bath is 25%. The temperature of the heat treatment is 260°C, and the length of the high-temperature resistant meta-aramid short fibers is 8 mm.

[0107] (4) The high temperature resistant meta-aramid chopped fibers are placed in deionized water and stirred, and a second dispersant with a mass concentration of 0.1% is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2%; the meta-aramid fibrils are beaten and dispersed to obtain a meta-aramid fibril slurry with a mass concentration of 0.5%; the high temperature resistant meta-aramid chopped fiber slurry with a mass concentration of 0.2% and the meta-aramid fibril slurry with a mass concentration of 0.5% are mixed and stirred uniformly to obtain a mixed slurry; the second dispersant is polyethylene oxide.

[0108] (5) The mixed slurry of step (4) is conveyed to a double-layer composite inclined wire paper machine for papermaking. After the bottom wire wet paper web is formed, the aramid nanofiber dispersion is evenly sprayed on the upper surface of the bottom wire wet paper web by a pressure spraying device, and then the aramid nanofiber is composited with the top wire wet paper web so that the aramid nanofiber is located between the bottom wire wet paper web and the top wire wet paper web. After pressing and drying, an aramid paper base is obtained. The aramid nanofiber is a meta-aramid nanofiber with a diameter of 50 nm. The aramid nanofiber dispersion comprises aramid nanofiber and deionized water, wherein the mass fraction of the aramid nanofiber is 0.14%.

[0109] (6) The aramid paper base obtained in step (5) is fully dried and preheated by a channel-type hot drying device, and then enters a roller hot press for two hot pressing processes, wherein the first hot pressing process is high temperature and low pressure, and the second hot pressing process is low temperature and high pressure. After the hot pressing process is completed, an aramid paper for honeycomb core material is obtained. The set temperature of the drying channel drying device is 210°C, the temperature of the first hot pressing process is 310°C, the pressure is 170N / mm, and the vehicle speed is 25m / min, and the temperature of the second hot pressing process is 240°C, the pressure is 360N / mm, and the vehicle speed is 25m / min.

[0110] The aramid paper samples prepared in the above examples and comparative examples were subjected to relevant performance tests before and after being impregnated with resin. The impregnated resin was phenolic resin (PR type) provided by Nantong Sumitomo Bakelite Co., Ltd. The specific test results are shown in Table 1 below. The specific test methods involved are: According to GB / T 451.2-2002 standard, the quantitative test of aramid paper samples was carried out, and the amount of impregnation and gluing was calculated according to (quantity after impregnation - quantity before impregnation) / quantity before impregnation.

[0111] The tear strength of aramid paper samples was tested according to GB / T455-2001 standard.

[0112] Table 1 Performance test data of aramid paper obtained in the examples and comparative examples

[0113] According to the data in Table 1, Examples 1-5 all exhibited a relatively low amount of impregnation sizing, indicating that the overall density of the aramid paper was good, and the tear strength before and after impregnation was able to maintain a relatively high level.

[0114] From the comparison of the data of Comparative Example 1 and Example 5, it can be seen that if aramid nanofibers are not added during the papermaking process, the amount of impregnation glue on the aramid paper increases significantly, and the tear strength before and after impregnation is also at a low level, which shows that aramid nanofibers can reduce the porosity of aramid paper and reduce the amount of resin entering the interior of the aramid paper.

[0115] From the comparison of the data of Comparative Example 2 and Example 5, it can be seen that: if the high-temperature resistant meta-aramid short fibers are not used but the conventional meta-aramid short fibers of the same size are used, the impregnation gluing amount of the aramid paper increases slightly, but the tear strength before and after the impregnation decreases significantly, which indicates that the high-temperature resistant meta-aramid short fibers prepared by the present invention can effectively improve the tear strength of the aramid paper before and after the impregnation with the resin.

[0116] From the comparison of the data of Comparative Example 3 and Example 5, it can be seen that if only one high-temperature and high-pressure hot pressing operation is performed, the amount of impregnation glue does not change significantly, but the tear strength before and after impregnation is significantly reduced, which shows that the high-temperature and high-pressure hot pressing method will cause a certain degree of damage to the strength and structure of aramid paper.

[0117] From the comparison of the data of Comparative Example 4 and Example 5, it can be seen that: when only one low-temperature and low-pressure hot pressing operation is performed, the amount of impregnation glue increases significantly, and the tear strength before and after impregnation decreases significantly, which indicates that the low-temperature and low-pressure hot pressing method cannot effectively plasticize the aramid paper, and the overall density and mechanical strength of the aramid paper are poor.

[0118] From the data comparison of Comparative Example 5, Comparative Example 6 and Example 5, it can be seen that if the high temperature resistant functional powder is only diethyl aluminum phosphite powder or only boron nitride powder, the tear strength before and after impregnation is significantly reduced, which shows that the combination of the two has a synergistic effect. When used alone, the strength and resistance to resin impregnation of aramid paper will decrease.

[0119] From the comparison of the data of Comparative Example 7 and Example 5, it can be seen that if the meta-aramid fibrids are not emulsified, the size of the aramid fibrids is too large, which is not conducive to the bonding between the aramid fibers, resulting in a small increase in the amount of aramid paper impregnation glue, and a significant decrease in the tear strength before and after impregnation.

[0120] From the comparison of the data of Comparative Example 8 and Example 5, it can be seen that if no oxygen plasma surface treatment is performed during the preparation of the high-temperature resistant meta-aramid chopped fibers, the hydrophilicity and surface activity of the high-temperature resistant meta-aramid chopped fibers are poor, which is not conducive to the dispersion of the fibers during the pulping process and the bonding between the aramid fibers, resulting in a significant increase in the amount of glue applied to the aramid paper after the resin is impregnated, and a significant decrease in the tear strength before and after the impregnation.

[0121] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0122] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing aramid paper for resin-impregnated honeycomb core material, characterized in that: The preparation method is: S1, adding the high temperature resistant functional powder and the first dispersant into a solvent and mixing them evenly to obtain a dispersion containing the high temperature resistant functional powder; and mixing the dispersion containing the high temperature resistant functional powder and the meta-aramid polymer solution evenly to obtain a spinning solution; The high temperature resistant functional powder is aluminum diethylphosphinate powder and boron nitride powder; S2, spinning the spinning solution by wet spinning, and then going through a high-temperature coagulation bath, a room-temperature coagulation bath, washing, drying, heat treatment, oxygen plasma surface treatment, curling and cutting process to obtain high-temperature resistant meta-aramid short fibers; S3, preparing a high temperature resistant meta-aramid chopped fiber slurry by mixing the high temperature resistant meta-aramid chopped fiber in water; preparing meta-aramid fibrid into meta-aramid fibrid slurry; The high temperature resistant meta-aramid chopped fiber slurry and the meta-aramid fibrid slurry are uniformly mixed to obtain a mixed slurry; S4, sending the mixed slurry to a double-layer composite inclined wire paper machine for papermaking, after the bottom wire wet paper web is formed, spraying the aramid nanofiber dispersion on the upper surface of the bottom wire wet paper web, and then compounding it with the surface wire wet paper web, so that the aramid nanofiber is located between the bottom wire wet paper web and the surface wire wet paper web, and obtaining the aramid paper base paper after pressing and drying; S5. After being dried and preheated, the aramid base paper is subjected to two hot pressing processes to obtain the aramid paper for the resin impregnation resistant honeycomb core material.

2. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In step S1, the mass ratio of the aluminum diethylphosphinate powder to the boron nitride powder is 1:(2-3); The first dispersant is any one of polymethacrylic acid and polyvinyl pyrrolidone.

3. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In step S1, the solvent in the meta-aramid polymer solution is N,N-dimethylformamide; the solvent for preparing the dispersion is N,N-dimethylformamide; The meta-aramid polymer solution has a solid content of 25-28% and a viscosity of 450-650P at 25°C; The mass content of the high temperature resistant functional powder in the dispersion is 20-35%, and the mass content of the first dispersant in the dispersion is 1.0-2.5%; The mass ratio of the dispersion to the meta-aramid polymer solution is 1:(13-18).

4. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In step S2, the temperature of the high temperature coagulation bath is 50-90°C, the high temperature coagulation bath is N,N-dimethylformamide and water, and the mass concentration of N,N-dimethylformamide in the coagulation bath is 28-32%; The temperature of the room temperature coagulation bath is 20-30° C. The room temperature coagulation bath is N,N-dimethylformamide and water. The mass concentration of N,N-dimethylformamide in the room temperature coagulation bath is 25-30%.

5. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In step S2, the heat treatment temperature is 250-350°C; the oxygen plasma surface treatment equipment is an inductively coupled plasma generator, the treatment frequency is 1000-1300 Hz, and the treatment time is 8-10 min; the length of the high temperature resistant meta-aramid chopped fibers is 5-8 mm.

6. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In step S3, the preparation method of the high temperature resistant meta-aramid short fiber slurry is as follows: the high temperature resistant meta-aramid short fiber is placed in deionized water for stirring, and a second dispersant is added to disperse the fibers uniformly to obtain a high temperature resistant meta-aramid short fiber slurry with a mass concentration of 0.2%-1.0%, wherein the mass content of the second dispersant in the high temperature resistant meta-aramid short fiber slurry is 0.1-0.5%; the second dispersant is any one of polyethylene oxide and polyacrylamide; The preparation method of the meta-aramid fibrillation slurry is as follows: the meta-aramid fibrillation is emulsified by a high-speed shearing emulsifier, the processing speed is 13000-15000rpm, and the processing time is 10-15min; then the meta-aramid fibrillation slurry with a mass concentration of 0.5%-1.5% is prepared by beating and dispersing; the size distribution of the meta-aramid fibrillation is 40-120 meshes.

7. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: The aramid nanofiber dispersion comprises aramid nanofibers and deionized water, wherein the mass fraction of the aramid nanofibers in the aramid nanofiber dispersion is 0.05-0.20%; The aramid nanofiber is any one of meta-aramid nanofiber and para-aramid nanofiber, and the diameter of the aramid nanofiber is 40-100 nm.

8. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In step S5, drying and preheating are performed using a drying tunnel drying device, and the drying and preheating temperature is 200-260°C; The two hot pressing steps include a first high-temperature and low-pressure hot pressing operation and a second low-temperature and high-pressure hot pressing operation. The temperature of the first high-temperature and low-pressure hot pressing operation is 290-340°C, the pressure is 120-180N / mm, and the vehicle speed is 15-30m / min; the temperature of the second low-temperature and high-pressure hot pressing operation is 230-270°C, the pressure is 350-400N / mm, and the vehicle speed is 15~30m / min.

9. The method for preparing the aramid paper for the resin impregnation resistant honeycomb core material according to claim 1, characterized in that: In the process of preparing the aramid paper, the meta-aramid fibrids are 30-50 parts by weight, the high temperature resistant meta-aramid chopped fibers are 50-70 parts by weight, and the aramid nanofibers are 8-15 parts by weight.

10. A resin-impregnated aramid paper for honeycomb core material, characterized in that: The aramid paper is prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Special aramid paper for aramid paper honeycomb and preparation method of special aramid paper

    CN114211847A

  • Preparation method of heat-conducting aramid insulation paper for high-frequency and high-voltage electrical equipment

    CN114875709A

  • Aramid insulation paper-based material for motor slot insulation and preparation method of aramid insulation paper-based material

    CN115506176A

  • Preparation method of aramid honeycomb paper-based material with low porosity and low air permeability

    CN116732812A

  • Electrical insulating paper

    US20130277089A1